Absence of calretinin protein expression in malignant mesotheliomas from asbestos-exposed NF2(+/−) mice and mouse mesothelioma cell lines from various mouse strains - Blum, Walter (Biomark Res, 2018)
BACKGROUND: Calretinin is the most widespread positive marker for the immunohistochemical identification of malignant mesothelioma (MM) and was proposed to serve as a blood-based biomarker. Functionally, evidence has accumulated that calretinin might be implicated in MM tumorigenesis. We aimed to identify calretinin (CR; Calb2) in murine MM and reactive mesothelial cells in granuloma from asbestos-exposed NF2(+/−) mice, a line heterozygous for the tumor suppressor merlin (NF2), used as a mouse MM model. Additionally, we sought to ascertain the presence of calretinin in MM cell lines from other mouse strains. We also intended to investigate the role of calretinin in mesotheliomagenesis by comparing the survival of asbestos-exposed NF2(+/−) and NF2(+/-)CR(−/−) mice. METHODS: NF2(+/−) and NF2(+/-)CR(−/−) mice, both lines on a C57Bl/6J background, were exposed to asbestos following an established protocol. Tumor histology and asbestos-induced mortality were assessed. MM and granuloma from NF2(+/−) mice were analyzed with immunohistochemical methods for calretinin expression. Levels of Calb2 mRNA and calretinin expression in tumors and MM cell lines of various mouse strains were determined by RT-qPCR and Western blot analysis, respectively. RESULTS: No expression of calretinin at the protein level was detected, neither in MM from NF2(+/−) mice, NF2(+/−) MM-derived cell lines nor immortalized mesothelial cells of mouse origin. At the mRNA level we detected Calb2 expression in MM cell lines from different mouse strains. Survival of NF2(+/−) and NF2(+/-)CR(−/−) mice exposed to asbestos showed no significant difference in a log-rank (Kaplan-Meier) comparison. CONCLUSIONS: The concomitant determination of calretinin and mesothelin blood levels has been proposed for early detection of human MM. Mouse MM models based on asbestos exposure are assumed to yield helpful information on the time course of appearance of mesothelin and calretinin in the blood of asbestos-treated mice determining the earliest time point for interventions. However, the observed absence of calretinin in MM from NF2(+/−) mice and derived cell lines, as well as from MM cells from Balb/c and C3H mice likely precludes the use of calretinin as a biomarker for mouse MM. The results also indicate possible species differences with respect to an involvement of calretinin in the formation of MM.